2018
DOI: 10.1111/crj.12750
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma in Iranian adults: The first national survey and the most recent updates

Abstract: The prevalence of asthma in Iran was similar to other Asian and European countries. However, repeated national surveys are required to determine the trend of asthma prevalence in Iran in comparison to other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
7
24
3
Order By: Relevance
“…However, our study estimate was lower than that reported by a national survey in Iran, using symptoms of wheezing with dyspnea, as 9.4%; and also somewhat lower when using their definition of ‘current asthma’ which included asthma attack or use of asthma medications i.e. 4.7% [ 8 ]. Obel et al reported asthma burden to be 6.9% in a population based survey from sub-Saharan Africa using self-reported asthma-ever and and/or receiving asthma medications, which is higher than in our study [ 25 ].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…However, our study estimate was lower than that reported by a national survey in Iran, using symptoms of wheezing with dyspnea, as 9.4%; and also somewhat lower when using their definition of ‘current asthma’ which included asthma attack or use of asthma medications i.e. 4.7% [ 8 ]. Obel et al reported asthma burden to be 6.9% in a population based survey from sub-Saharan Africa using self-reported asthma-ever and and/or receiving asthma medications, which is higher than in our study [ 25 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Allergy has been commonly reported risk factor across many studies and established associations have also been found for high Serum IgE level, a substitute for allergic sensitization, and for common allergens identified by skin prick tests with asthma [ 3 , 30 ]. A nationally representative survey among Iranian adults showed that prevalence of asthma was significantly higher among the older age group [ 8 ]. This finding is comparable to the INSEARCH survey from India which determined significant relationship with advancing age, highlighting a possible “cumulative effect” of age, including asthma diagnosed in past, besides late onset of the disease [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal alternations and gender‐specific differences in environmental exposures have been proposed as the possible explanations for this change just about puberty. However, such difference was not detected neither in the Iranian adult population as recently reported nor in any of the subgroups participated in this study. It seems that asthma is more prevalent in males both in the adult and paediatric populations.…”
Section: Discussioncontrasting
confidence: 73%
“…To the best of our knowledge, this is the first national survey on the prevalence of asthma and asthma symptoms in Iranian children aged 6‐7 and 13‐14 years which was performed along with our recently published study, determining the prevalence of adult asthma in Iran . A relatively large sample of 33 260 children was evaluated in two subgroups of individuals with different ages.…”
Section: Discussionmentioning
confidence: 99%